Sustainability Accounting in the Bantengan Community: Integrating the Triple Bottom Line with Local Government Support - Sopanah, Ana; Bahri, Syamsul; Sulistyan, Riza Bahtiar; Khasanah, Midhatul (Universitas Pendidikan Ganesha, 2025)
The purpose of this research to explores sustainability accounting within the Bantengan traditional art community by utilizing the Triple Bottom Line (TBL) framework, which are economic, social, and environmental aspects. It reveals that the Bantengan community possesses informal and culturally specific financial practices that reflect their local values. Despite the absence of formal accounting systems, the community engages in self-help initiatives, show an awareness of financial sustainability through collective social actions like mutual support and environmental preservation. This research highlighted the necessity for collaboration between the Bantengan community and their local government. The current collaboration tends to be more bureaucratic, lacking ongoing technical assistance. The findings indicate a significant potential to integrate local wisdom into sustainable practices, which can enhance community resilience and help preserve cultural heritage. The research recommends that participatory governance models be established, allowing community members to engage actively in decision-making. This approach fosters ownership and accountability in sustainability efforts, finally supporting both cultural preservation and the financial viability of the Bantengan tradition.